A comparative analysis of associated injuries in the elderly and youth for facial fractures. Issue 6 (June 2022) - Diab, Jason; Flapper, Walter; Grave, Benjamin; Moore, Mark H
Abstract: Introduction: High-velocity and high-impact forces can yield life-threatening injuries that are not only limited to the face but can involve other regions of the body. Associated injuries are more frequent in the elderly impacting management and outcomes. The primary objective was to study the association between associated injuries and age groups by identifying epidemiological trends and differences among the elderly and younger population. Methods: A retrospective review was conducted from January 2012 to January 2017 at the Royal Adelaide Hospital, Adelaide. A comparative analysis for elderly and younger controls was assessed for associated injuries, etiology, management, and length of stay. Results: There were 355 elderly and 1884 younger controls for the study. There were differences between gender, alcohol, socioeconomic status, type of facial fracture, mechanism of injury, and associated injuries ( p <0.05). The elderly were 3.6 times more likely to have an associated injury compared to the younger cohort ( p <0.05). Total limb injuries were 2.2 times more likely in the elderly compared to the younger cohort, and neurological related injuries were 2.7 times more likely ( p <0.05). Neurological injuries were most frequent in fall-related injuries, limb injuries in RTA; and soft-tissue injuries for assault, sport, animal, and work ( p <0.001). The elderly had longer hospital stays as compared with younger controls ( p <0.05). Conclusions: Associated injuries are more frequent in the elderly and impact other bodily systems leading to a longer length of stay. In the assessment and management of facial trauma, anatomical and disciplinary boundaries may cross requiring interdisciplinary care.